2016
DOI: 10.25077/jka.v5i1.467
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Karakteristik Ibu dengan Pemilihan Kontrasepsi di Puskesmas Padang Pasir Padang

Abstract: AbstrakPemerintah berupaya menekan laju pertumbuhan Indonesia dengan melaksanakan program Keluarga Berencana (KB) yang tercantum dalam Rencana Pembangunan Jangka Menengah (RPJM) tahun 2004-2009 adalah meningkatkan penggunaan kontrasepsi jangka panjang. Saat ini terdapat berbagai metode kontrasepsi. Banyak wanita mengalami kesulitan dalam memilih kontrasepsi. Tujuan penelitian ini adalah menentukan hubungan karakteristik ibu dengan pemilihan kontrasepsi. Jenis penelitian yang digunakan bersifat deskriptif anali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 1 publication
1
4
2
7
Order By: Relevance
“…Someone who has a higher education level will be broader and easier to accept ideas, more independent and rational in making decisions and actions (Jurisman, Ariadi, & Kurniati, 2016). In contrast to research conducted by Gosavi, et al, Who found that education levels did not have a significant relationship with the selection of contraceptives.…”
Section: Discussionmentioning
confidence: 68%
“…Someone who has a higher education level will be broader and easier to accept ideas, more independent and rational in making decisions and actions (Jurisman, Ariadi, & Kurniati, 2016). In contrast to research conducted by Gosavi, et al, Who found that education levels did not have a significant relationship with the selection of contraceptives.…”
Section: Discussionmentioning
confidence: 68%
“…6 Jurisman et al found that most of IUD users IUD were in the age group of 20-35 years. 7 Bleeding and abdominal pain are the side effects that are caused by the reaction in the endometrium plasminogen. Nidhi et al found that on intracesarean IUD, 15 subjects had bleeding, while 88% had only mild pain.…”
Section: Discussionmentioning
confidence: 99%
“…Variabel yang paling berpengaruh terhadap pemilihan metode kontrasepsi jangka panjang adalah adalah sikap (Setiasih et al, 2016). Tingkat pendidikan memiliki hubungan yang bermakna dengan pemilihan kontrasepsi, seseorang dengan tingkat pendidikan tinggi cenderung memilih kontrasepsi IUD (Jurisman, Ariadi, & Kurniati, 2016). Ibu yang menggunakan kontrasepsi KB suntik adalah 44 orang (29,5%).…”
Section: Pembahasanunclassified